2019
DOI: 10.1155/2019/8162975
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Change in Sodium and Potassium Ion Concentrations in Stored Donor Blood and Their Effect on Electrolyte Balance of Recipients

Abstract: Background Preserved blood cells undergo progressive structural and functional changes that may affect their function, integrity, and viability after transfusion. The impact of transfusion of stored blood on potassium, sodium, or acid-base balance in the recipient may be complex, but information on it is inconsistent. This study therefore sought to determine the changes in the potassium and sodium levels in whole blood stored at 4°C for 28 days and clinical outcomes when such blood are transfused. Methods Whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 13 publications
7
16
0
Order By: Relevance
“…Oxidative processes, as noted by other researchers, can stimulate lipid peroxidation, protein Band 3 clustering, [14,25,26], discontinuities in cytoskeleton filaments, polymerization and aggregation of the protein structures of the matrix network [27]. In our study, extracellular К + concentration increased up to 10–12 m m (3·4 m m initially) due to violations of the lipid bilayer membrane, lactate increased and glucose decreased, which is consistent with other studies [3,28–30]. Such changes at the molecular level can cause impairments in the cytoskeleton structure and increasing of E during storage of pRBCs observed by us (Figs.…”
Section: Discussionsupporting
confidence: 91%
“…Oxidative processes, as noted by other researchers, can stimulate lipid peroxidation, protein Band 3 clustering, [14,25,26], discontinuities in cytoskeleton filaments, polymerization and aggregation of the protein structures of the matrix network [27]. In our study, extracellular К + concentration increased up to 10–12 m m (3·4 m m initially) due to violations of the lipid bilayer membrane, lactate increased and glucose decreased, which is consistent with other studies [3,28–30]. Such changes at the molecular level can cause impairments in the cytoskeleton structure and increasing of E during storage of pRBCs observed by us (Figs.…”
Section: Discussionsupporting
confidence: 91%
“…This potentially emergency practice is regularly utilized in term infants for suppressing the occurrence of acute bilirubin encephalopathy (ABE), kernicterus features, and death (20). Reversible electrolyte imbalances, especially natural serum sodium and potassium disturbances, are the two most increasingly frequent abnormalities that are referred for administration of ECT therapy (14). To the best of the authors' knowledge, there are a few conducted quantitative and qualitative surveys for determining and improving the increased risk of detrimental clinical outcomes correlated with possible fatal abrupt changes in sodium during and after the exchange transfusion in newborns.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have reported that the most important reason of the apparent sodium ion concentration change near the upper limit of standard value in most cases, during and after exchange blood transfusion, is poor nutrition in the first several days of life that leads to physiological loss of extracellular fluid's volume, body water imbalance, and dehydration (5,(12)(13)(14). Additionally, serum sodium ion concentration disturbances following administration of an extensive quantity of stored blood products, which are typically sodium bicarbonate-rich solutions, could be deduced as poor prognosis of renal failure (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…SLs are responsible for negative post-transfusion effects in recipients, particularly in critically ill patients, and are classified into three categories: biochemical, biomechanical or morphological, and immunological changes [ 4 ]. Particularly, biochemical changes include the increase of potassium and sodium and hemolysis and oxidative injury [ 1 , 2 , 5 , 6 , 7 , 8 ]; biomechanical or morphological modifications include shape alterations and a reduction of RBC deformability. The modifications related to the corpuscular components of blood units could relate to RBC, white blood cells (WBCs) and platelets (PLTs).…”
Section: Introductionmentioning
confidence: 99%
“…The modifications related to the corpuscular components of blood units could relate to RBC, white blood cells (WBCs) and platelets (PLTs). Those related to RBCs are oxidative injury [ 7 ], hemolysis [ 2 , 6 ], morphological alterations and changes in membrane composition [ 1 ], changes in sodium and potassium levels [ 1 , 5 , 8 ], and the release of procoagulant microparticles [ 9 , 10 ]; those connected to WBCs and PLTs are the increase in interleukin (Il-8) and VEGF [ 11 , 12 , 13 ], and the release of procoagulant phospholipid (PPL) [ 14 ] and microparticles [ 15 ].…”
Section: Introductionmentioning
confidence: 99%